(untitled) (Research, Society and Development, 2020)
Introduction: Due to the culturally determined standards of beauty and aesthetics, the smile should be harmonious and pleasant. The presence of anterior teeth with disharmony in shape and size, agenesis or even diastema become the complaints most reported by patients. Thus, with the advances in adhesive systems, composite resins are being increasingly used in dentistry, aiming to solve esthetic problems in anterior teeth. Objective: To report the clinical protocol for closing diastemas. Case Report: A female patient sought care to resolve the space between the central incisors. It was decided to use the direct adhesive restorative system, so prior prophylaxis and the choice of the color of the composite resin was performed. Then, application of phosphoric acid and adhesive, according to the manufacturer’s recommendations. Subsequently, the composite resin was applied using the incremental technique with the aid of the polyester matrix, finishing and polishing. Conclusion: Restoration with composite resin allows to restore aesthetics and achieve smile harmony, being considered a viable clinical procedure for closing diastema.